THE COVID-19 CRISIS, RISK COMPLIANCE AND ITS AFTERMATH ON PROFESSIONAL ACCOUNTANTS - Kaka, Emmanuel John (School of Accountancy, University of Agung Podomoro, 2020)
The accounting profession has always assisted to support and shape private and public businesses. Butthe fast pace at which the outbreak of covid-19 crisis has broad changes in the use of digitaltechnology in businesses, post a great challenges to the accountants and their firms. To overcome therisk and challenges, accountants must add value by embracing digital technology to meet the currentand future challenges. The paper is aim at exposing accountants to the risk compliance and aftermathof covid-19 in the way they deliver their services. The method used in data collection was secondarysources. Areas trashed by the paper includes risk and compliance challenge, risk management to beconsidered during crisis, the need for effective crisis management by the accountant, accountantstoolkit for managing covid-19,and technology a must have. The study concludes that digital technologyis a must have for professional accountants if really they want to be relevant and stay in business inthis period of pandemic and in the future.